Risk of recurrent hepatic encephalopathy in patients with liver cirrhosis: a German registry study. Issue 9 (September 2021) - Gabriel, Maria M.; Kircheis, Gerald; Hardtke, Svenja; Markwardt, Daniel; Buggisch, Peter; Mix, Heiko; Grüngreiff, Kurt; Welzel, Tanja M.; Kälsch, Julia; Hartmann, Heinz; Gerbes, Alexander L.; Karpowitz, Maria v.; et al.
Abstract : Background and aims: Patients with hepatic encephalopathy (HE) show low quality of life, recurrent hospitalizations and an increased mortality. We aimed to assess the natural course of patients after a recent episode of overt HE and to identify risk factors for HE recurrence in Germany. Methods: Fifteen sites took part in a prospective, observational study including patients with liver cirrhosis who had been hospitalized for HE within 3 months before recruitment. Clinical data, psychometric hepatic encephalopathy score (PHES) and critical flicker frequency were assessed quarterly for 1 year. Primary endpoint was HE recurrence requiring hospitalization, all-cause-mortality was treated as a competing risk factor. Results: From January 2014 to March 2016, a total of 115 patients were recruited. Overall 14 premature deaths were documented. For 78 subjects follow-up data were available in accordance with the protocol. After a median of 118 days, more than half of the per-protocol cohort was readmitted to hospital due to HE (N = 34) or died (N = 11). The risk for hospitalization was significantly increased in patients who had been recruited by liver transplant centers ( P = 0.003), had had frequent HE relapses prior to recruitment ( P = <0.0001) or an abnormal PHES result of <−4 ( P = 0.044). Abnormal PHES results barely missed level of significance as an independent risk factor for re-hospitalization in a multivariable competing risk model ( P = 0.093). Conclusion: Patients with a history of HE are at high risk for the development of recurrent overt HE demanding hospitalization. The PHES test may aid in detection, monitoring and risk stratification of recurrent HE. Abstract : Supplemental Digital Content is available in the text.